Prevalence and Types of Anemia among Patients with Colorectal Cancer at Tripoli University Hospital, Libya - Nasef , Bushra; Abdulwahed, Eman; Nasr, Narjis; Al-Zanad, Balqis; Nasef , Faraj; Nuuail , Nuri (AlQalam Journal of Medical and Applied Sciences, 2026)
Anemia is a common and clinically significant complication among patients with colorectal cancer (CRC), often resulting from chronic gastrointestinal blood loss, tumor-associated inflammation, or iron metabolism disturbances. Despite its prognostic and diagnostic relevance, data on anemia prevalence and types among Libyan CRC patients are scarce. This study aimed to evaluate the prevalence and morphological types of anemia among Libyan colorectal cancer patients before and after chemotherapy and to examine their association with disease stage, tumor site, demographic factors, history of rectal bleeding, and changes in hemoglobin levels following treatment. A retrospective cross-sectional study was conducted at the Oncology Department of Tripoli University Hospital, including 156 patients diagnosed with CRC during 2023–2024. Demographic, clinical, and hematological data were collected from medical records. Anemia was defined according to WHO criteria (Hb <13 g/dL for males, <12 g/dL for females). RBC indices (MCV and MCHC) were used to classify anemia. Associations with clinical and demographic variables were assessed using Chi-square and t-tests; p < 0.05 was considered significant. The mean age at diagnosis was 60.6 ± 11.9 years, with 56.4% males. The most common tumor sites were rectum (21.8%), rectosigmoid (19.2%), and sigmoid colon (16.7%). Stage IV was the most frequent at diagnosis (41.0%). Pre-chemotherapy, mean hemoglobin was 11.70 ± 1.72 g/dL, with anemia prevalence of 70.5%, slightly higher in males (75.0%) than females (64.7%, p = 0.162). Anemia prevalence did not differ significantly by age group, tumor site, or cancer stage. Patients with a history of rectal bleeding had significantly higher anemia prevalence (80.0% vs. 54.2%; p = 0.002). Normocytic normochromic anemia predominated (≈63%), followed by microcytic hypochromic (≈33%) and macrocytic (<1%). Post-chemotherapy (n = 122), mean hemoglobin was 11.89 ± 1.64 g/dL, and anemia persisted in 59.0% of patients, mostly normocytic normochromic (77.8%), with minor increases in microcytic (16.7%) and macrocytic (5.6%) patterns. Anemia is highly prevalent among Libyan CRC patients, predominantly normocytic normochromic, and is significantly associated with a history of rectal bleeding. Despite chemotherapy, a substantial proportion remain anemic, underscoring the importance of early detection, continuous monitoring, and targeted management of anemia in this population.